Faktor- Faktor yang Mempengaruhi Kadar Hemoglobin pada Mahasiswa - Novita Dewi; Errick Endra Cita (Jurnal Akademika Baiturrahim Jambi, 2026)
Anemia remains a common health problem and can be influenced by various physiological factors and lifestyle behaviors. This study aimed to analyze factors associated with hemoglobin (Hb) level among respondents. This research used a quantitative approach with bivariate and multivariate analyses. The Chi-square test was applied to analyze categorical variables, while the Independent Samples T-Test was used for numerical variables. Furthermore, logistic regression analysis was conducted to determine the simultaneous effect of independent variables on Hb status. The variables examined included sex, age, portion and frequency of meals, peripheral oxygen saturation (SpO₂), and exercise duration. The results of the bivariate analysis showed that none of the variables had a significant relationship with Hb status (p > 0.05). However, the multivariate analysis indicated that age (p = 0.021) had a significant association with Hb status, while the other variables did not show a significant relationship. Future studies are recommended to involve a larger sample size, include additional variables such as iron intake, nutritional status, and physical activity patterns, and apply a longitudinal research design to better explain causal relationships